Evaluation of substance addiction with depressive personality patterns in the therapy process: case analysis - Öztürk, Güneş (Journal of Dependence, 2022)
Although there are different perspectives on the psychological causes of substance abuse, it is accepted as an undoubted fact that an addict has problems in object relations, weakness in himself and basic defenses. Clinical studies show that the prevalence of personality disorder is high in populations with substance use disorders. However, it is thought that it is a common illusion for therapists in the field to focus on the problem of substance addiction and evaluate the client in the addictive personality structure, and they often overlook the possibility of another personality disorder accompanying the client while planning the therapy. Since the optimal therapeutic style suitable for each personality type is different from each other, it was thought that distinguishing personality disorders is a critical issue in the increase or decrease of the patient’s complaints when planning the treatment. This study aims to explain the causes of substance addiction through the depressive personality structure. It is desired to emphasize that for a substance addict with a depressive personality organization, whether the substance is experienced as a reward for achieving pleasure or as a punishment given to the badly experienced self can change the course of the therapeutic intervention. The study is to draw the attention of therapists to the main dynamics that push the client to addiction, the emergence of symptoms of personality disorder and the new meanings of the substance according to the client’s personality organization, based on the client’s anamnesis information. In this context, in this study, the client is explained through impulse, defense, self and object relations. It is thought that the study will be beneficial for drug addicts and therapists working outside of pharmacological treatment.